2013
DOI: 10.1080/15389588.2012.759654
|View full text |Cite
|
Sign up to set email alerts
|

Cyclist–Motorist Crash Patterns in Denmark: A Latent Class Clustering Approach

Abstract: The latent class clustering approach provided a comprehensive and clear map of cyclist-motorist crash patterns. The results are useful for prioritizing and resolving safety issues in urban areas, where there is a significant share of cyclists potentially involved in multiple hazardous situations or where extensive bicycle sharing programs are planned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 61 publications
(32 citation statements)
references
References 42 publications
2
30
0
Order By: Relevance
“…Crash reports contained information about characteristics of the crash (e.g., crash type, injury severity, time of day, day of the week, infrastructure characteristics, land use, light conditions, weather conditions), involved vehicles (e.g. make, model, maneuvers prior to the crash, registration date, collision point), and injured persons (e.g., injury severity, demographics, alcohol or drug use, seat belt or helmet use, license status) (for details, see Kaplan and Prato, 2013;Kaplan and Prato, 2014). Crash injury severity reporting of these types of crashes in police records in Denmark as well as other countries (see, e.g., Aertsens et al 2010;Elvik and Mysen 1999;Juhra et al 2012;Veisten et al 2007).…”
Section: Datamentioning
confidence: 99%
“…Crash reports contained information about characteristics of the crash (e.g., crash type, injury severity, time of day, day of the week, infrastructure characteristics, land use, light conditions, weather conditions), involved vehicles (e.g. make, model, maneuvers prior to the crash, registration date, collision point), and injured persons (e.g., injury severity, demographics, alcohol or drug use, seat belt or helmet use, license status) (for details, see Kaplan and Prato, 2013;Kaplan and Prato, 2014). Crash injury severity reporting of these types of crashes in police records in Denmark as well as other countries (see, e.g., Aertsens et al 2010;Elvik and Mysen 1999;Juhra et al 2012;Veisten et al 2007).…”
Section: Datamentioning
confidence: 99%
“…Concerning the former, a couple of studies revealed that increasing levels of van, large automobile, and truck traffic were associated with higher collision risks (Ackery, McLellan, & Redelmeier, 2012;Vandenbulcke et al, 2014). Compared to cars, buses and heavy vehicles have more blind spots and cyclists in the blind spot of a huge goods vehicle entailed higher a risk of collisions (McCarthy & Gilbert, 1996), especially when buses and heavy vehicles turned right at intersections (Kaplan & Giacomo Prato, 2013;Vandenbulcke et al, 2014). Larger size of the vehicle contributes to increase the risk of BMV collisions because of a more cumbersome manoeuvrability as well as and increased presence of blind spots.…”
Section: Vehiclementioning
confidence: 99%
“…Crashes were extracted from the National Crash Database that the Danish Road Directorate compiles from police reports. These reports enclose information about the characteristics of the crash, the injured persons and the involved vehicles (for details, see, e.g., 34,35). Most importantly, these reports contain a georeferenced location of the crashes that enables matching them with the road network.…”
Section: Datamentioning
confidence: 99%